Kinetics of Gas Carburizing of Zr–1%Nb Alloy - Trush, V. S.; Pohrelyuk, I. M.; Lyk’yanenko, A. G.; Kravchyshyn, T. M.; Fedirko, V. M.; Korendii, V. M.; Kovalchuk, I. V. (Materials science (New York, N.Y.), 2024)
The kinetic characteristics of thin-sheet (approx. 1 mm) Zr–1%Nb alloy samples after treatment in a carbon-containing gas medium ( P Ar + C 3 H 8 = 0.106 Pa) in a wide temperature range of 650–850°C and time 1; 5 and 10 h were investigated. The carburizing of the alloy at temperatures of 650 and 750°C occurs according to a law close to linear ( n ≈ 1), and at 850°C according to a law close to parabolic ( n ≈ 2). The activation energy of the alloy carburizing in the temperature range of 650–850°C at the propane partial pressure p C 3 H 8 = 0.018 Pa was 2.21 kJ/mol. The distribution of microhardness and structure of the near-surface layers of the alloy was shown. The microstructure of the near-surface layers of the alloy after carburizing was determined. The α-Zr and ZrC phase content on the alloy surface after treatment in a carbon-containing gas environment is presented.